Late diagnosis of sickle cell disease in adults still a challenge in developing countries: a case report - Venance Emmanuel Mswelo; Kayiira Mubaraka; Yasa Mohamed; Peter Kyaligonza; Elias Joseph Xwatsal (Journal of Medical Case Reports, 2024)
Abstract Background Sickle cell disease is a genetic disease with multisystem involvement. More than 300,000 children are born with sickle cell disease globally, with the majority of cases being in Sub-Saharan Africa. In Uganda, about 20,000 children are born with sickle cell disease annually, with more than three-quarters dying before the age of 5 years. Those who live beyond 5 years tend to have poor health-related quality of life, numerous complications, and recurrent hospitalizations. In developing countries, most symptomatic patients are diagnosed early in childhood. Few of those not screened in childhood tend to present in adulthood with variable symptoms. Case presentation This case reports a 22-year-old African male patient of Toro tribe who presented with paroxysms of multiple joint pain associated with generalized body malaise for about 6 months. He presented as a referral from a lower facility with an unestablished cause of symptoms. Physical examination revealed conjunctival pallor, icterus, and tenderness of joints. Cell counts showed anemia and hemoglobin electrophoresis revealed 87% of sickled hemoglobin. Conclusion This case report pinpoints the importance of considering the diagnosis of sickle cell disease even in adults presenting with symptoms of sickle cell disease. It also adds to the relevance of screening at all age groups, especially in high-endemic regions such as Africa and Asia.